Prevalence of and associated risk factors for pterygium in the high altitude communities of Upper Mustang, Nepal - Maharjan, IM; Shreshth, E; Gurung, B; Karmacharya, S (Nepalese Journal of Ophthalmology, 2014)
Objective: To determine the prevalenceof and associated risk factors for pterygiumin the high altitude communities of the Upper Mustang region of Nepal, near the Tibet border. Materials and methods: Six villages of the Upper Mustang were selected based on the concentration of population. All subjects were permanent residents aged 16 years and older, and recruited through a household census with mobilization of local monks who had been trained as interviewers, and people were invited to attend the eye clinic for a complete examination. A cross-sectional studywas conducted which included the parameters oflaterality, severity, occupation, age, sex and altitude of residence. Results:The study population comprised 1,319 individuals of which 637 (48.29%) weremale and682 (51.71%) were female.The overall prevalence of pterygium, was 10.08% (133 of 1,319), with 42.86% for males and 57.14% for females. The mean age of the subjects was45.83 years and the mean SD 17.94. The majority of the subjects had a unilateral pterygium. The right eye(n=63) was predominately affected, in 57.80% of the total subjects. Farmers and construction workers, which comprised of 36.09% and 28.57% respectively, had a higher prevalence of pterygium. The most affected age group was the 66 to 75 years group (n=31: 23.31%). The prevalence increased linearly with age. The severe Grade III and Grade IV pterygium were predominant in the age group of 56-65 years, comprising 28.58% of all the cases;the less severe Grade I was also predominant in the same age group,with 23.56%, and Grade II (0-2 mm) was predominant in the age group of 46-55, with 31.03%. Conclusion: Pterygiumisa significant public health problem in the high altitude communities of Nepal. It is more prevalent amongst the farmers than in the other professionals. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10774 Nepal J Ophthalmol 2014; 6 (2): 65-70